Incisional hernia: incidence, clinical profile, risk factors and prevention - JG, Sharath Kumar; K, Upendra Kumar; Manangi, Mallikarjuna; KP, Madhu; BJ, Arun; Nagaraj, Niranjan (International Surgery Journal, 2016)
Background:Incisional hernias are very common. They are the second most common type of hernia after inguinal hernias. This study was undertaken to study the incidence and various risk factors leading to incisional hernia. Methods: This prospective study was conducted in department of surgery, Sri Devaraj URS Medical College, Kolar, India from May 2010 to May 2012. All the cases were analyzed in various aspects like age, sex, parity, relative incidence, clinical presentation, nature of previous operation, site of previous scar, precipitating factors like obesity, wound infection, abdominal distension. Results:The incidence is around 7.5%. Patients in the age group of 30-60 years found to have highest incidence of incisional hernia. Females outnumbered the males with the ratio of 4:1. Incisional hernia was more common in patients with previous history of gynecological operation. Most of the patients presented with incisional hernia in the infra umbilical region. Conclusions:Incisional hernias are iatrogenic and preventable by avoidance of midline incisions, especially in the infra umbilical region.